Histone Lysine and Genomic Targets of Histone Acetyltransferases in Mammals. (24th August 2018) - Voss, Anne K.; Thomas, Tim
Abstract : Histone acetylation has been recognized as an important post‐translational modification of core nucleosomal histones that changes access to the chromatin to allow gene transcription, DNA replication, and repair. Histone acetyltransferases were initially identified as co‐activators that link DNA‐binding transcription factors to the general transcriptional machinery. Over the years, more chromatin‐binding modes have been discovered suggesting direct interaction of histone acetyltransferases and their protein complex partners with histone proteins. While much progress has been made in characterizing histone acetyltransferase complexes biochemically, cell‐free activity assay results are often at odds with in‐cell histone acetyltransferase activities. In‐cell studies suggest specific histone lysine targets, but broad recruitment modes, apparently not relying on specific DNA sequences, but on chromatin of a specific functional state. Here we review the evidence for general versus specific roles of individual nuclear lysine acetyltransferases in light of in vivo and in vitro data in the mammalian system. Abstract : Recruitment of HATs by DNA‐binding transcription factors suggested specificity for subsets of genes (A). Chromatin‐binding domains within HAT protein complexes indicate recruitment to chromatin of a specific functional state, supported by HAT occupancy of many or most active genes (B). Within cells, individual HATs acetylate (Ac) specific histone lysine residues.